Efforts of the Bandung Polrestabes Traffic Accident Unit in Utilizing CCTV as an Evidence Tool in Disclosing Traffic Accidents - Budiman, Muhamad Arif (Indonesian Journal of Police Studies, 2024)
This research is motivated by the existence of problems in CCTV (Closed Circuit Television) in traffic accidents that occur in the jurisdiction of Polrestabes Bandung. Traffic accidents that occur issue a number of factors, because they are not proficient in driving, unconsciousness, and inadequate CCTV. CCTV Records Traffic CCTV (Closed Circuit Television) Records More Than Those Using CCTV Records. Theories Purchased Information Technology Theories, Performance Theories, Management Theories, and Competency Theories in a Frame Using CCTV (Closed Circuit Television) Bandung Research using qualitative with field research conducted through interviews, observations and document studies , which then results in this research being analyzed by validating the data of research findings according to explanations of nara sources, organizing data in accordance with questions related to research, presenting data, validating data in accordance with theory and rejecting data. The results of this study show the collaboration between Bandung Polrestabes and related institutions BCC, ATCS by utilizing CCTV (Closed Circuit Television) as evidence in complaints of traffic accidents and factors related to the use of CCTV (Closed Circuit Television) as evidence. The research studies are: CCTV (Closed Circuit Television) installation that is added at an invisible point, is making and arranging CCTV picket schedules, and approved by members who have not been well approved by CCTV (Closed Circuit Television) to be given additional training such as Dikjur or training held by the West Java Regional Police.